Selection of Philippine Plant Oils as Possible Feedstocks for Biodiesel - Razon, Luis F. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
By using fatty acid profiles from literature, 27 plant species found in the Philippines were evaluated for their potential to provide feedstock for the production of biodiesel. Of the 27 considered, 15 plant species were found to have the potential of providing biodiesel that will conform to the biodiesel standards of the European Standard Organization (CEN) and the American Society for Testing Materials (ASTM):Adenanthera pavonina, Calotropis gigantea, Calotropis procera, Canarium luzonicum, Canarium odontophyllum, Canarium ovatum pulp, Cerbera manghas, Cleome viscosa, Cryptostegia grandiflora, Dacryodes rostrata, Nephelium mutabile, Ptychosperma macarthuri, Psophocarpus tetragonolobus, Raphanus sativus and Sapindus saponaria.